Stella & Marigold - Barrows, Annie; Blackall, Sophie (Chronicle Books, 2024)
Two sisters, Stella and Marigold, share adventures (both real and imagined) and secret sister things. Stella, who$1 (Bs seven, is kind, a good storyteller, and ponders big questions like, what do animals think of people? Marigold, at four, tells imaginative stories (her mother calls them (3z(Bfibs(3y(B) and likes to wear her favorite Halloween costume year-round. Stella and Marigold do all the regular things$1 (Blike going to school, playing, getting sick sometimes, and visiting the zoo$1 (Bbut even the most regular things have a secret side.s
Ages 5-8.
Keywords: Sisters -- Juvenile fiction; Imagination -- Juvenile fiction; Family life -- Juvenile fiction